2014
DOI: 10.1016/j.jvoice.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analyses of Elicited Modal, Raised, and Pressed Rabbit Phonation

Abstract: Objectives/Hypothesis The purpose of this study was to use nonlinear dynamic analysis methods such as phase space portraits and correlation dimension (D2) as well as descriptive spectrographic analyses to characterize acoustic signals produced during evoked rabbit phonation. Methods Seventeen New Zealand white breeder rabbits were used to perform the study. A Grass S-88 stimulator (SA Instrumentation, Encinitas, CA) and constant current isolation unit (Grass Telefactor, model PSIU6; West Warwick, RI) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
(66 reference statements)
2
7
1
1
Order By: Relevance
“…Acoustic analysis of elicited phonation samples revealed vocal intensity and fundamental frequency values that are consistent with modal intensity phonation using pulsed electrical stimulation . Sound spectrograms from the present study revealed modal intensity‐elicited phonations, characterized by strong harmonics and rare occurrences of aperiodicity, as described previously . Additionally, the aerodynamic properties of elicited phonations, notably airflow rate and subglottal pressure, are in congruence with expectations for rabbit‐evoked modal intensity phonation.…”
Section: Discussionsupporting
confidence: 89%
“…Acoustic analysis of elicited phonation samples revealed vocal intensity and fundamental frequency values that are consistent with modal intensity phonation using pulsed electrical stimulation . Sound spectrograms from the present study revealed modal intensity‐elicited phonations, characterized by strong harmonics and rare occurrences of aperiodicity, as described previously . Additionally, the aerodynamic properties of elicited phonations, notably airflow rate and subglottal pressure, are in congruence with expectations for rabbit‐evoked modal intensity phonation.…”
Section: Discussionsupporting
confidence: 89%
“…However, Mills et al (2017) achieved phonation at lower flow rates starting from $17 mls À1 . Also the experiments reported by Awan et al (2014) showed good consistency with our experiments regarding flow rates (85 mls À1 -144 mls À1 ). However, we could apply flow rates of up to 180 mls À1 (25% higher) yielding regular vibrations.…”
Section: A Histologysupporting
confidence: 89%
“…One study focused on establishing the ex vivo, and another the in vivo, rabbit model as a feasible model for phonatory analysis (Maytag et al, 2013;Ge et al, 2009). Awan et al (2014) analyzed in vivo nonlinear dynamic phenomena by varying flow rate and adduction levels. However, only one ex vivo study performed detailed parameter studies (Mills et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Nonlinear dynamic measurements such as correlation dimension (D2) or largest Lyapunov exponent are successful in differentiating between normal and irregular phonations, while traditional perturbation methods fail. 912 Recently, Sprecher (2010) introduced the addition of a fourth voice type. This scheme reclassified type 3 voice as chaotic with a finite dimension, and defined type 4 voice as chaotic with infinite dimension.…”
Section: Introductionmentioning
confidence: 99%